Long Lamai community ICT4D E‐commerce system modelling: an agent oriented role‐based approach - Cheah, Wai Shiang; Abdul Halin, Alfian; Lu, Marlene; CheeWhye, Gary (Department of Information Systems, City University of Hong Kong, 2016)
This paper presents the post‐mortem report upon completion of the Long Lamai e‐commerce development project. Some weaknesses with regards to the current software modelling approach are identified and an alternative role‐based approach is proposed. We argue that the existing software modelling technique is not suitable for modelling, making it difficult to establish a good contract between stakeholders causing delays in the project delivery. The role‐based approach is able to explicitly highlight the responsibilities among stakeholders, while also forming the contract agreement among them leading towards sustainable ICT4D.